2006
DOI: 10.1038/sj.bjc.6603079
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of irinotecan combined with carboplatin in previously untreated small-cell lung cancer

Abstract: To determine the efficacy and toxicity of irinotecan combined with carboplatin, we conducted a phase II trial. Eligibility criteria were: chemotherapy-naïve, small-cell lung cancer (SCLC), good performance status (PS: 0 -2), agep75 years, and adequate organ function. The patients' characteristics were: male/female ¼ 56/5; PS 0/1/2 ¼ 19/38/4; median age (range) ¼ 68 years(51 -75 years); limited disease (LD)/extensive disease (ED) ¼ 27/34. The patients received irinotecan (50 mg m À2 ) on days 1, 8, and 15, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…These results are very encouraging and superior to other trials with similar irinotecan dosages and schedules. Grade 3/4 toxicities were 50% in neutropenia and 29.6% in diarrhoea, and were comparable with previous other trials (Kudoh et al, 1998;Noda et al, 2002;Hanna et al, 2006;Kinoshita et al, 2006). However, one treatmentrelated death was observed in this trial.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are very encouraging and superior to other trials with similar irinotecan dosages and schedules. Grade 3/4 toxicities were 50% in neutropenia and 29.6% in diarrhoea, and were comparable with previous other trials (Kudoh et al, 1998;Noda et al, 2002;Hanna et al, 2006;Kinoshita et al, 2006). However, one treatmentrelated death was observed in this trial.…”
Section: Discussionsupporting
confidence: 90%
“…Kudoh et al (1998) reported that combination chemotherapy of irinotecan and cisplatin (IP) in patients with SCLC showed a promising response rate of 84 with 29% of complete responses and median survival over 13 months. Since then, several phase II/III trials of irinotecan-based combination chemotherapy with different dose and schedule were performed with varying results in SCLC patients (Noda et al, 2002;Kudoh et al, 2005;Hanna et al, 2006;Kinoshita et al, 2006;Schmittel et al, 2006). In a previous phase III trial conducted by a Japanese group, patients were treated with 60 mg m À2 of cisplatin on day 1 and 60 mg m À2 of irinotecan on days 1, 8, and 15 every 4 weeks, and showed a good median survival of 12.8 months.…”
mentioning
confidence: 99%
“…The efficacy data in our trial are comparable with that observed in previous phase II trials. In previous phase II trials, RR ranged from 69 to 79% and PFS ranged from 5.4 to 6.4 months with an OS of 9.7-11.0 months when patients were treated with irinotecan (50 mg/m 2 on days 1, 8, and 15) and carboplatin (AUC 5) [30,31]. The higher dose of irinotecan in our trial was not associated with an obvious improvement in therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 86%
“…The hematologic toxicity observed likely demonstrates the potential additive myelosuppressive effects of irinotecan (and/or its metabolites) in previously treated patients. Multiple dosing schedules of the combination of irinotecan and carboplatin have been studied in adults with a variety of malignancies, [25][26][27] including lung cancer, [29][30][31] ovarian cancer, 28 and non-Hodgkins lymphoma. 41 As in the current study, the main toxicities were gastrointestinal and hematologic, and efficacy in phase 1 of 2 studies has been encouraging.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Toxicities are mostly nonoverlapping; however, the combination can result in enhanced myelosuppression. Given the single-agent efficacy of carboplatin and irinotecan in a variety of pediatric tumors and the promising experience in adults, this combination is worthy of evaluation in pediatric patients with recurrent solid tumors.…”
mentioning
confidence: 99%